Psychological Features of Learning in The Process of Education (Eurasian Journal of Learning and Academic Teaching, 2022)
The article examines the psychological features of learning in the process of education, the factors that determine students' attitudes to the subject, discusses the need for conscious assimilation of learning motives, the formation of positive attitudes among students, interest in disciplines.